FRI0074 The Patient Global Assessment of Disease Activity in Rheumatoid Arthritis: Identification of Underlying Latent Factors Using Principal Components Analysis. (15th July 2016) - Challa, D.N.V.; Kvrgic, Z.; Crowson, C.S.; Matteson, E.L.; Mason, T.G.; Persellin, S.T.; Michet, C.J.; Wampler Muskardin, T.; Wright, K.; Davis, J.M.
Abstract : Background: The patient global assessment of disease activity is a crucial component of validated disease activity scores, response criteria, and the ACR/EULAR definition of remission in rheumatoid arthritis (RA). Recent work has shown that the patient global reflects persistent undifferentiated symptoms of pain, fatigue, and functional disability, occasionally despite seeming attainment of low inflammatory disease activity. The absence of a conceptual framework for evaluating patients in this scenario is a critical barrier to improving patient-centered outcomes. Objectives: To identify underlying latent factors driving the patient global assessment of disease activity using a quantitative, multivariable data reduction approach. Methods: This was a prospective cross-sectional study of 70 patients with RA fulfilling the ACR/EULAR 2010 classification criteria. Data were collected from the most recent rheumatology visit, including the patient and provider global assessments of disease activity (0–100 mm), tender and swollen joint counts, and current RA drug therapies. The patient sample was stratified to include 50 "discordant" patients (i.e., patient global assessments of disease activity were ≥25 mm higher than the provider global assessments) and 20 "concordant" patients. Co-morbid anxiety, depression, osteoarthritis, and fibromyalgia by provider diagnosis were abstracted from the complete electronic medical records. Participants completed several validated patient-reported outcome measures (PROMs), including measures of pain and pain interference, fibromyalgia, physical function, ability to participate, anxiety, depression, and fatigue. Data were evaluated using exploratory principal component analysis (PCA) as a data reduction method to determine the latent constructs in the data. Linear regression models were then used to determine the variability in patient global assessment explained by the PCA scores. Results: The 70 patients had a mean age of 61 years, mean RA duration of 8.0 years, and 73% were female. The mean Clinical Disease Activity Index was 12.9. The mean (SD) for the patient global assessment of disease activity was 44.6 (22.7) and for the provider global assessment was 20.1 (17.7). PCA yielded 8 factor scores that represented domains of pain, fatigue, anxiety, depression, advanced age and degenerative arthritis, physical disability, fibromyalgia, and unknown. Linear regression analysis showed that pain explained the greatest variability in the patient global assessment of any of the factor scores (adjusted R-squared value: 0.06). The factor scores for pain, depression and anxiety, inability to participate, fibromyalgia, and advanced age were all significantly associated with the patient global assessment and altogether explained 33% of the variability in the patient global assessment. Conclusions: Pain, depression and anxiety symptoms, inability to participate, fibromyalgia, and advanced age are key drivers of the patient global assessment. Future studies are warranted to develop a standardized approach to management of these factors toward the realization of patient-centered treat-to-target strategies for RA. Disclosure of Interest: None declared